Strategi Pembelajaran Berbasis Active Learning dalam Konteks Pendidikan Agama Islam - Yusi Srihartini; Noerlitasari; Titono Wahyudi (Ikatan Dai Indonesia, 2025)
The shift towards 21st-century learning paradigms necessitates the implementation of instructional strategies that emphasize not only cognitive development but also affective and psychomotor domains. This study explores the theoretical and practical foundations of active learning strategies within Islamic Religious Education (IRE) contexts. Using a qualitative-descriptive approach through literature review, the study examines the conceptual framework, pedagogical principles, instructional components, implementation models, and pedagogical benefits of active learning in religious education settings. Findings reveal that active learning transforms students from passive recipients to engaged participants through various activities, such as group discussions, simulations, collaborative tasks, guided teaching, jigsaw techniques, and student-generated case studies. The effectiveness of these strategies lies in the activation of learners’ cognitive, emotional, and social engagement, supported by motivational dynamics, experiential learning, social interaction, reflection, and feedback mechanisms. In IRE classrooms, this approach facilitates deeper value internalization, practical religious skill-building, and higher student motivation. Moreover, active learning supports the cultivation of 21st-century competencies including critical thinking, collaboration, creativity, and problem-solving. Successful implementation, however, requires pedagogical readiness, strategic instructional planning, and a supportive classroom environment. Therefore, integrating active learning into IRE curricula is not only pedagogically relevant but also essential in shaping reflective, autonomous, and character-driven learners.